2023
DOI: 10.1002/adma.202204413
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive Supramolecular Polymers: From Light‐Controlled Small Molecules to Smart Materials

Abstract: and metal-ligand complexation [24] are attractive noncovalent interactions to enable the formation of supramolecular polymers. There are diverse groups that offer proper hydrogen bonds, for instance, amide, urea, ureidopyrimidinone (UPy), and barbituric acid derivatives. [13][14][15][16]25] Perylene bisimides and naphthalene bisimides are widely used in supramolecular polymers to provide π-π stacking moieties. [17,18] Pyridine and pyrrole are extensively studied units to coordinate with metals, i.e., Pt II , Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 279 publications
0
71
0
1
Order By: Relevance
“…Therefore, these results reveal that light stimulated P Cu -DPQ have atypical self-assembled 2D nanosheets with crystallinity among others. Additionally, P Cu -DPQ entails distinct charge separation in donor and acceptor which promotes the potential structure for improvement of electronic properties in organic electronics. …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these results reveal that light stimulated P Cu -DPQ have atypical self-assembled 2D nanosheets with crystallinity among others. Additionally, P Cu -DPQ entails distinct charge separation in donor and acceptor which promotes the potential structure for improvement of electronic properties in organic electronics. …”
Section: Resultsmentioning
confidence: 99%
“…For the latter types of energy-driven molecular systems, the next necessary step is transmission of directional motions to places further away from where these motions are initially generated . This can be done in an up-scaling fashion by the transmission of the geometric state changes to an ordered environment, e.g., liquid crystals, , polymers, , or on surfaces . However, in less organized environments such as simple liquid solvents, transmission of motions at the molecular scale needs to be controlled more tightly in order not to diffuse the directional motion away by the action of the Brownian storm.…”
Section: Introductionmentioning
confidence: 99%
“…31−34 To date, numerous outstanding studies have been conducted on novel photoresponsive polymers bearing azobenzene groups as side chains for applications in the fabrication of functional devices and smart surfaces. 35,36 For example, Tian et al reported a simple strategy for the fabrication of novel photoresponsive semiconductor devices via incorporation of two types of azobenzene groups in the side chain of the conjugated D−A polymer. 37 Li et al synthesized two kinds of azobenzene side-chain polymers with photoswitchable chiroptical properties, which have potential application in the development of functional optoelectronic devices.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among them, photoresponsive materials have attracted extensive attention because light is a kind of green and environmentally friendly clean energy that can be regulated remotely, rapidly, and accurately. Compared to the photoresponsive inorganic transition-metal oxide, photoresponsive organic molecules with reversible conformational changes, such as spiropyran, , diarylethenes, , and azobenzene, have been widely used in controllable liquid transport, information storage, sensors, anticounterfeiting, , etc. In particular, the azobenzene and its derivatives demonstrate the obvious variation of the spatial structure and the dipole moments between the stable trans state and the metastable cis state, which endows the azobenzene-containing materials with fascinating properties of a reversible structural change or surface properties upon photoirradiation. To date, numerous outstanding studies have been conducted on novel photoresponsive polymers bearing azobenzene groups as side chains for applications in the fabrication of functional devices and smart surfaces. , For example, Tian et al reported a simple strategy for the fabrication of novel photoresponsive semiconductor devices via incorporation of two types of azobenzene groups in the side chain of the conjugated D–A polymer . Li et al synthesized two kinds of azobenzene side-chain polymers with photoswitchable chiroptical properties, which have potential application in the development of functional optoelectronic devices .…”
Section: Introductionmentioning
confidence: 99%